Cell‐Based Bio‐Hybrid Delivery System for Disease Treatments. Issue 10 (9th July 2021) - Li, Chu-Xin; Qi, Yong-Dan; Feng, Jun; Zhang, Xian-Zheng
Abstract : Live cells are implicated in diverse biological processes, including nutrient transport and removal of foreign substances. Their intelligent biofunctions with complex mechanisms cannot be replicated at all in man‐made materials despite the significant advance in material design. Taking advantages of their biocompatibility and biotropic capability, various live cells have been developed as a kind of special carriers for the on‐demand delivery of therapeutic and diagnostic agents in recent years. Furthermore, synthetic materials can be integrated with live cells to provide bio‐hybrid systems that inherit advantages from both the synthetic particles and the natural cells. Herein, recent strategies and advances in cell‐based bio‐hybrid delivery systems for disease treatment are summarized. Challenges and opportunities in this field are also discussed. Abstract : Bio‐hybrid delivery systems based on integration of living cells and synthetic materials are widely explored for disease and tumor treatment. Herein, the recent studies, prevalent strategies, as well as clinical studies on the topic of cell‐based bio‐hybrid system are introduced. Potential problems are also discussed, and prospects for the development and improvement in this fieldare provided.